Globalization and the welfare state - Yay, Gulsun Gurkan; Aksoy, Tolga (SPRINGER, 2018)
This paper analyzes the impact of globalization on the Welfare State (WS). Some argue that globalization poses a serious threat to WS and therefore questions its sustainability. On the other hand, some others suggest that WS has to expand more as economies are integrating. After reviewing different hypothesis on the relationship between globalization and WS, we empirically examine the relationship by using 32 countries covering 1980 through 2010. According to the estimation results, there is no direct linkage between globalization and the WS. However the reaction of the WS against globalization is found to vary dramatically depending on welfare regimes. We find evidence in favor of compensation hypothesis in Social Democrat, Conservative and Mediterranean Welfare State regimes, whereas efficiency effect is in place in liberal Welfare States.
Keywords: Globalization; Welfare state; Social security expenditures; KOF index; ECONOMIC GLOBALIZATION; CROSS-SECTION; COUNTRIES; POLITICS; OPENNESS; REGIMES; GROWTH; REFORM; OECD; Social Sciences - Other Topics; Mathematics